Effects of optimal pacing strategies for 400-, 800-, and 1500-m races on the VO2 response - Hanon, C.; Thomas, C. (Journal of Sports Sciences, 2011)
The aim of this study was to compare the evolution of oxygen uptake (VO2) in specifically trained runners during running tests based on the 400-, 800-, and 1500-m pacing strategies adopted by elite runners to optimize performance. Final velocity decreased significantly for all three distances, with the slowest velocity in the last 100 m expressed relative to the peak velocity observed in the 400 m (77%), 800 m (88%), and 1500 m (96%). Relative to the previously determined VO2max values, the respective VOO2peak corresponded to 94% (400 m) and 100% (800 and 1500 m). In the last 100 m, a decrease in VO2 was observed in all participants for the 400-m (15.6 ± 6.5%) and 800-m races (9.9 ± 6.3%), whereas a non-systematic decrease (3.6 ± 7.6%) was noted for the 1500 m. The amplitude of this decrease was correlated with the reduction in tidal volume recorded during the last 100 m of each distance (r = 0.85, P < 0.0001) and with maximal blood lactate concentrations after the three races (r = 0.55, P < 0.005). The present data demonstrate that the 800 m is similar to the 400 m in terms of decreases in velocity and VO2.